The impact of Netflix's data collection on its consumer and their satisfaction - Bisiaux, Juliette; Kumar, Prashant; Vimolwan Yukongdi; Ransom, Lakeesha K.; EDHEC Business School, France; Asian Institute of Technology (2021)
This master research study aims at exploring the impact of Netflix data collection of its customer and their satisfaction. Surely, the new giant of the entertainment industry based its competitive advantage on its consumer's data, to build strong content recommendation system and producing original content. As it is supposed to match their taste and increase their satisfaction. However, it has created new consumptions behaviors and to some extent it can have some negative impact on consumers. Then, to know if these new ways of distributing content could really impact positively consumer's satisfaction, had to be deepen. The purpose of this study is to identify if the Netflix recommendation system as well as original content created with data collection impact positively the consumer's satisfaction. A survey was designed thanks to the software Qualtrics which helped to measure customer satisfaction for the two research problems and to answer the hypotheses. The analysis permitted to say that Netflix recommendation system and original content impact positively the consumer satisfaction and thus, data collection for the platform can help them being impactful. Yet, this impact did not seem strong and obvious, especially for the recommendation system.
A research submitted in partial fulfillment of the requirements for the degree of Master of Business Administration
Research Studies Project Report (M.B.A.) - Asian Institute of Technology, 2021
Keywords: Netflix (Firm); Consumer satisfaction; Data collection systems